ON THE BEHAVIOR OF POLARIZED LIGHT IN TWIST-ORIENTED NEMATIC LIQUID CRYSTALS WITH ANISOTROPIC ABSORBENT DYE - Hovakimyan, H.H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2020)
In this work we study the propagation of light in a twist-oriented pleochroic nematic liquid crystal with pleochroic dye. The dependence of the intensity of transmitted light on the azimuthal angle of the linearly polarized incoming light has been investigated experimentally. As a result, the role of absorption anisotropy has been identified.